Fertility and feeding of Tamarixia triozae (Hymenoptera: Eulophidae) on potato psyllid Bactericera cockerelli - Cerón-González Claudia; Lomeli-Flores, J. Refugio; Rodríguez-Leyva Esteban; Torres-Ruíz Alfonso (Revista Mexicana de Ciencias Agrícolas, 2018)
Tamarixia triozae is an ectoparasitoid that feeds on its host, the potato psyllid (Bactericera cockerelli), this gives advantage as a biological control agent because it removes psyllid nymphs for oviposition and predation. In order to determine the potential of T. Triozae in regulating populations of B. cockerelli, in this study the mean fertility and predatory capacity was determined under laboratory conditions (25 ± 1 °C, 70 ± 10% RH and 12:12 h L: D). The females of T. Trioza and lived 30.9 days (10-59 days). Each female nymphs consumed on average 181 (31-529 nymphs) and had a mean of 130 eggs fertility (28-316 eggs), which implies that each egg to produce a female requires consuming on average 1.39 nymphs of B. cockerelli.